1994
DOI: 10.1128/jb.176.23.7267-7273.1994
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations causing overexpression of RNA polymerase alpha subunit on regulation of virulence factors in Bordetella pertussis

Abstract: In Bordetella pertussis, expression of virulence factors is controlled by the Bvg proteins, which comprise a sensor-regulator two-component signal transduction system. Previously, we described a mutant strain of B.pertussis that had reduced transcription of pertussis toxin and adenylate cyclase toxin genes, while other virulence factors were relatively unaffected. We obtained a B. pertussis clone that repaired the defect in both this strain and an independent mutant strain with a similar phenotype when introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
33
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…Mutations affecting only Ptx or Cya expression mapped in or near ptx or cya, respectively, while mutations affecting Ptx and Cya expression mapped at or near bvg or rpoA (18). Mutations mapping to the rpoA locus of B. pertussis which have a Ptx-Cya-Fha' phenotype have recently been described (6,7,31). This paper describes the further characterization of two mutations which were mapped to the bvg locus.…”
Section: Discussionmentioning
confidence: 98%
“…Mutations affecting only Ptx or Cya expression mapped in or near ptx or cya, respectively, while mutations affecting Ptx and Cya expression mapped at or near bvg or rpoA (18). Mutations mapping to the rpoA locus of B. pertussis which have a Ptx-Cya-Fha' phenotype have recently been described (6,7,31). This paper describes the further characterization of two mutations which were mapped to the bvg locus.…”
Section: Discussionmentioning
confidence: 98%
“…This has led to speculation that the bvg virulence control system may have a downstream activator that participates in ptxA expression, much like the ToxRS-ToxT regulatory system of Vibrio cholerae (13). Several mutations conferring an Fha ϩ Cya Ϫ Ptx Ϫ phenotype have been isolated and mapped (9,48). These mutations are not located in a putative downstream transcriptional activator but are instead found upstream of the translational start site of rpoA or in the C terminus of BvgA, invoking a model in which BvgA interacts with RpoA at the ptxA promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, initial reports indicated that bvgAS was not sufficient for activation of ptxA and cya transcriptional fusions in E. coli (17,33). These results suggested that an intermediate factor was required for expression of pertussis toxin and adenylate cyclase; however, such a factor has not yet been described (9,31,48). …”
mentioning
confidence: 97%
“…The resulting BamHI fragment was then cloned into the allelic exchange vector pSS1129. The resulting construct, pSS1129-DcspB, was transferred by conjugation into B. bronchiseptica, and selection for double-crossover events was carried out as described elsewhere (Carbonetti et al, 1994;Stibitz & Yang, 1991). The resulting cspB deletion mutant was termed BB7865DcspB.…”
Section: Methodsmentioning
confidence: 99%